UPAYA PT.UNILEVER INDONESIA TBK DALAM MENGATASI PENCEMARAN LINGKUNGAN HIDUP DI INDONESIA PADA TAHUN 2015-2019 - Apriliahaq, Nurul Cahyani; ", Afrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
As a developing country, Indonesia is faced with environmental problems that occur within its country. According to the Indonesian Ministry of Environment and Forestry, it was stated that Indonesia suffered some environmental pollution problems that fluctuating especially in the year 2015-2019, because this affects the survival of people in Indonesia, hence the need for help from various actors to help overcome the problem.The research uses the corporate Social Responsibility (CSR) theory, with a green thought perspective supported by the concept of sustainable development (SDGs). The study also used qualitative descriptive research methods and the level of behavioral analysis of the group. Research data is obtained through literature review and all research data comes directly from official government web pages and related official websites.Based on the research analysis, the conclusion is that the efforts of PT.Unilever Indonesia Tbk in overcoming environmental pollution in Indonesia is run through the USLP program. This Program is a follow-up of corporate CSR obligations that have been regulated in government and statutory regulations. Realization of this program focuses on efforts to build a sustainable business and aligned with the natural order PT. Unilever Indonesia Tbk can establish a profitable and lasting business cooperation.Â Keywords: Environmental Sustainability, Efforts, Corporate Social Responsibility (CSR), Overcoming Environmental pollution, PT.Unilever Indonesia Tbk, Sustainable Development (SDGs).